Non-medical pathways to cardiovascular health: a discourse analysis of dietary and lifestyle interventions in the United States (Journal of Ideas in Health, 2025)
Background: Cardiovascular diseases (CVD) are a leading cause of morbidity and mortality in the United States. While conventional medical treatments dominate cardiovascular care, non-medical pathways, such as plant-based dietary patterns and lifestyle modifications, have gained recognition for their potential to complement traditional approaches.Methods: A qualitative discourse analysis was conducted on peer-reviewed articles published between 2013 and 2023. A systematic search across databases identified 10 studies that met inclusion criteria, focusing on non-medical interventions for reducing CVD risk in U.S.-based populations. Data extraction and thematic synthesis highlighted key patterns related to dietary and lifestyle interventions, cost implications, physiological outcomes, and implementation barriers.Results: Five key themes emerged from the analysis: (1) Plant-based dietary patterns, including vegetarian and vegan diets, consistently improved blood pressure and lipid profiles. (2) Lifestyle modifications, such as increased physical activity and stress management, enhanced cardiovascular health when integrated into primary care frameworks. (3) Non-medical interventions demonstrated significant improvements in physiological outcomes, including reductions in systolic and diastolic blood pressure. (4) These interventions were cost-effective and scalable, making them viable options for diverse populations. (5) Barriers to implementation included cultural and socioeconomic factors, as well as challenges in sustaining long-term adherence.Conclusion: Non-medical pathways, particularly plant-based dietary patterns and lifestyle modifications, play a critical role in mitigating cardiovascular disease risks. These approaches not only address key physiological risk factors but also provide cost-effective, accessible, and scalable solutions for diverse populations. Overcoming barriers to implementation through tailored interventions and community-based strategies is essential to ensure their success. Integrating these non-medical pathways into healthcare frameworks could significantly reduce the burden of CVD and promote equitable health outcomes.
Keywords: Cardiovascular Health, Qualitative Discourse Analysis, Dietary and Lifestyle Interventions, United State, United Kingdom